The influence of size effects on thin films local piezoelectric response of thin films - Morozovska, A.N.; Svechnikov, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
We discuss the influence of size effects on the local piezoelectric response of thin films. In calculations of the electrostatic potential in the triple system “PFM probe tip – film – substrate,” the effective point charge model is used. The obtained expressions for the local piezoelectric response of a surface layer (film) capped are intended for the calculations of Piezoresponse Force Microscopy signals of thin polar films epitaxially grown on thick substrates. Theoretical predictions are in qualitative agreement with typical experimental results obtained for perovskite Pb(Zr, Ti)O₃ and multiferroic BiFeO₃ films.